Temporal conidial dispersal pattern of Botryosphaeriaceae species in table-grape vineyards in Northeastern Brazil - SILVA, Fabio; SANTOS, Kledson; RÊGO, Tamiris; ARMENGOL, Josep; ROSSI, Vittorio; MICHEREFF, Sami; Gonzalez-DOMINGUEZ, Elisa (Phytopathologia Mediterranea, 2019)
A field experiment was conducted between mid-August 2016 and mid-October 2017 in four table-grape vineyards in the Siriji Valley, Pernambuco State (Northeastern Brazil), to study the conidial dispersal dynamics of Botryosphaeriaceae fungi, causing grapevine trunk diseases (GTDs). Conidial dispersal was assessed by exposing microscope slides coated with Vaseline close to symptomatic plants and pruning debris. The slides were replaced every 2 weeks for a total of 30 sampling periods. Conidia of the genera Diplodia, Lasiodiplodia and Neofusicoccum were enumerated based on morphological characters. Conidia were collected from all four table-grape vineyards, confirming that these fungi are present as aerial inoculum and could be associated with GTDs in the region. Conidia of Diplodia and Lasiodiplodia were present in all the sampling periods, and those of Lasiodiplodia were the most abundant. Conidia of Neofusicoccum were found less frequently, and in less numbers than the other genera. Significant correlation between the number of conidia sampled and the amount of rain was observed for Diplodia only. Greater numbers of conidia were collected from pruning debris than from symptomatic plants. For Diplodia and Lasiodiplodia, the numbers of conidia gradually increased in September, increased sharply between March and June, and then decreased. These dynamics were described by a logistic equation, with hydro-thermal time (i.e., a combination of degree-days and relative humidity) as the independent variable (R2 > 0.998).